الظّروف المخففة لمعقوبة بين الشريعة والقانون الجزائري - مرغني, أم الخير; برشاوة, إيمان; خادم, سميحة (University of Eloued-جامعة الوادي, 2014)
لقد أعطت الشّريعة الإسلامية والقوانين الوضعية لمجاني والأحوال التي يمر بها ظروف التّخفيف لمعقوبة لتحقيق العدل والصمح بين الأف ا رد . فالشّريعة الإسلامية والقانون الج ا زرر بيّنا أنّ لكل جريمة ظرفها الخاص بها، قد يكون هذا الظ رف ذ صمة بالجريمة وقد يكون لاحقا بها، أو ظرفاً ذاتيا متصلا بشخص الجاني وفي كل هذه الأحوال يستفيد من التخفيف. ولمّا كان أساس الشّريعة والقوانين الوضعية تحقيق العدل والمحافظة عمى النفس تركت هذه السمطة تقديرية لمقاضي لأنّ الظروف متغيِّرة ومتجددة، ولو كانت هذه الظروف مذكورة عمى سبيل الحصر لأصبح في تطبيق العقوبة ظمم واعتداء عمى الأف ا رد. Summary The Circumstances of mitigating the punishment have been taken in consideration by the Islamic Sharia, the reactionary laws of the offender and his state for achieving justice and reconciliation between individuals. Islamic Sharia and Algerian law make clear that each issue has its own circumstances. Whereas they may be linked or consequence to the crime, or self-connected to the offended person. Consequently, the offender benefits from these all mitigating circumstances .Therefore, the basis of Sharia and the justice lows are seeking justice and preserving the rights of the individuals the authority has been left to the judge in evaluating and assessing these circumstances. Because they are variable and renewed as if these conditions were confined and limited applying them would become injustice and esteem toindividuals.
شريعة وقانون